Where should I sing? Authority, space and choral voice in Seven against Thebes (Circe de clásicos y modernos, 2023)
The article aims to demonstrate that the spatial syntax of the scene between Eteocles and the chorus (vv. 78-368), crossed by the lament genre, constitutes a powerful, dynamic and programmatic mechanism to involve and guide the audience in relation to the action that unfolds, in a process that depends on the power of theater as a spectacle. It is argued that, in Seven against Thebes, the character –individual or collective– who rules over the space is the one who has power. In the studied scene, the taking of the space and the license to move in it are installed as a fundamental issue.
Keywords: Aeschylus; Seven against Thebes; chorus; space; authority